Determinants of Health Insurance Choice and Ownership in India-Evidence from National Sample Survey Data - Mauli Sanyal (European Scientific Journal, ESJ, 2025)
Out-of-pocket expenditure (OOPE) accounts for approximately 39% of total health expenditure in India and is on the rise. This is a matter of concern as high OOPE has impoverishing effects on the economy. Insurance serves as a cushion in the event of health-related distress and also helps consumers access the required quantity and better quality of care. Demand for insurance is a choice between risk and return that is contingent upon several socio-economic and demographic factors. The paper aims to identify the factors that influence the choice and ownership of health insurance in India.A multinomial logit model has been estimated using data on hospitalization published by the National Sample Survey Organisation, India (NSSO), 2014-15. Findings reveal that the presence of chronic ailments plays a significant role in the demand for health insurance. Other factors that not only shape demand but also influence the type of insurance chosen include education and income levels, household size and age of the individual. Government efforts have been crucial in reducing OOPE in India; however, better results can be expected with target-based innovative insurance products that offer greater coverage and transparency.